Beard Pulling in Medieval Christian Art: Various Interpretations of a Scene - Ekaterina Endoltseva; Andrey Vinogradov (Anastasis: Research in Medieval Culture and Art, 2016)
The article deals with the problem of interpretation of the scene where one person pulls the beard of another one or two persons pull the beard each other. These scenes are relatively widespread (Western Europe, Caucasus, Transcaucasia, Albania), their date is between VI and XII centuries. In result of the research some scenes are identified (“Joseph’s dream”, illustration to one of the apocryphal episodes of “Acts of John”). The possible meanings of the scenes in question are also specified.